Três ensaios em macroeconometria - Trompieri Neto, Nicolino (2009)
The thesis entitled "Três Ensaios em Macroeconometria" is composed of three chapters. The first chapter applies a dynamic panel model to analyze the convergence rate of growth of GDP per capita, non-linear approach using a threshold effect for the twenty-six Brazilian states plus the Distrito Federal during the period 1985-2005. The results indicate the existence of two convergence clubs, one formed by the states that are in the regime of low income, formed by the Northeast region, north (with the exception of the state of Amazonas) and the state of Goiás, while other club consists of those who are in the regime of income, formed by the states of South and Southeast, over the states of Mato Grosso, Mato Grosso do Sul and Distrito Federal. The second chapter presents a formulation of common trends in the variables real GDP, nominal interest rate Selic, money supply of M1 and IPCA inflation rate, to extract a measure of core inflation with features foward-looking. After determining the core inflation for the IPCA, we tested the conditions for a measure of core second Marques et al. (2003) along with two other core measures provided by the Banco Central do Brasil. Finally, we tested the accuracy of forecasts out of sample made by these measures to the IPCA. The results confirm that the measure of core inflation by common trends have a good predictive power. The third chapter tests the hypothesis of purchasing power parity (PPP) in Brazil during the period 1985 to 2008 by applying the unit root tests in panel with cross section dependence presented in Moon and Perron (2004) and Pesaran (2007 ). We tested the index of inflation INPC for nine metropolitan areas: Belo Horizonte, Belém, Curitiba, Fortaleza, Porto Alegre, Recife, Rio de Janeiro, São Paulo and Salvador. The results show a change in persistence after the Plano Real. While in the period of high inflation the PPP is satisfied, the period of stabilization of prices to PPP is not satisfied. This result is strengthened by examining the descriptive statistics of the data.